MILITARY CAMPAIGNS AND DIPLOMATIC STRATEGY OF EGYPT IN THE MIDDLE EAST IN THE ERA OF THE 18TH DYNASTY - Miryusuf Yusupov (Modern American Journals, 2025)
The article highlights the 18th Dynasty, the beginning of the New Kingdom. Egypt was a fragmented state and in decline, but with the rise of the 18th Dynasty, Egypt was able to restore its unity and become the most powerful nation. The pharaohs of the 18th Dynasty pursued an active foreign policy in the Middle East, as the Middle East was a strategically important region due to its trade routes for Egypt.
Keywords: New Kingdom, 18th Dynasty, diplomacy, Middle East, Ancient Egypt, military campaigns, Palestine, Syria